2022
DOI: 10.17275/per.22.44.9.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multicultural Education on Preservice Teachers’ Attitude and Efficacy: Testing Bank’s Content Integration Dimension

Abstract: The sudden increase in diversity in the public schools has caught teacher preparation institutions unprepared. The situation has led to a need to develop instructional interventions to help pre-service teachers get ready for a new context that they will be facing for the first time. Multicultural education can be of great importance to address the issues related to diversities. In order to create multicultural environments at schools, all the actors of the educational area need skills to better communicate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Multicultural education has been conceptualised in various ways [18] . According to Banks (2021), it encompasses three key aspects: a concept, a movement for educational reform, and an ongoing process aimed at providing equal learning opportunities for all students, irrespective of their social class, ethnicity, race, cultural background, gender, or sexual orientation.…”
Section: Multicultural Educationmentioning
confidence: 99%
“…Multicultural education has been conceptualised in various ways [18] . According to Banks (2021), it encompasses three key aspects: a concept, a movement for educational reform, and an ongoing process aimed at providing equal learning opportunities for all students, irrespective of their social class, ethnicity, race, cultural background, gender, or sexual orientation.…”
Section: Multicultural Educationmentioning
confidence: 99%
“…Research studies have reported many benefits of critical reflection in stimulating PSTs' PC development in the teaching and learning process of teacher education programs [39] [43]. The reflections made by EFL PSTs through the teaching practicum experience phase in schools resulted in their PC and behaviors that occurred in the school environment [8].…”
Section: Critical Reflection On Elt Practicum In Stimulating Psts' Pcmentioning
confidence: 99%
“…In addition, the critical reflection instilled in PSTs can show direction to stimulate the critical development of each individual [41]. When PSTs reflect on teaching practicum experiences to evaluate their attitudes, behavior, mentality, and competencies, it leads to new understandings and meanings for further development in PD [39] [43]. Furthermore, [34] and [30] reported that presenting content knowledge could not maximally provide PSTs as a problem-solving strategy.…”
Section: Critical Reflection On Elt Practicum In Stimulating Psts' Pcmentioning
confidence: 99%
“…They can feel rejected or not recognized for their identity and contribution. Fifth, Difficulties in communication: Different languages or different styles of communication can cause barriers to social interaction and intercultural understanding [6], [7]. Ineffective communication can deepen misunderstandings and conflicts.…”
Section: Introductionmentioning
confidence: 99%